Government Employee Perspectives on the Role of Tour de Borobudur in Creating Social Legacy - Ginting, Silvia Christin; Ali, Mohammad Arif; Rahayu, Tandiyo; Pornrattanachaichan, Pawatporn; Anggita, Gustiana Mega; Castyana, Billy; Yudhistira, Dewangga (JOSSAE (Journal of Sport Science and Education), 2024)
This article presents the findings of a study on the Tour de Borobudur events, focusing on its role in creating a social legacy from a governance perspective. The study utilized a descriptive quantitative research methodology to examine the perspectives of government employees on the management and utilization of sustainable tourism through the cycling race. The findings revealed a positive perception of the event’s impact on various aspects, including community communication, hospitality skills, managerial acumen, humanitarian aspects, and enthusiasm for sports and physical activity. The program was found to be a platform for improving communication skills, tourist service skills, local management abilities, and promoting an active lifestyle. The study recommends disseminating the findings to relevant stakeholders for the development of more effective programs and policies in the future, providing valuable insights for the government and the community in managing and harnessing tourism potential sustainably.